Development and psychometric testing of the Competence in Work Ability Risk Management and Analysis (Comp-WARMaA) instrument: a methodological study - Sirkka, Johanna; Suhonen, Riitta; Liira, Juha; Katajisto, Jouko; Stolt, Minna (BioMed Central, 2026)
Background: Work ability risk management and analysis (WARMA) requires professional competence to ensure effective, consistent, and high-quality occupational health nursing. Occupational health nurses (OHNs) play a central role in identifying and addressing work ability risks; however, no comprehensive instrument currently exists to assess their competence. This study aimed to develop and psychometrically evaluate such an instrument.
Methods: A descriptive, exploratory, and methodological design was applied. Instrument development followed a three-phase process comprising theory-based item generation, expert panel evaluations with consensus meetings, and empirical testing. Data were collected using two online surveys including the newly developed Competence in Work Ability Risk Management and Analysis (Comp-WARMaA) instrument. Psychometric properties were examined using classical and modern test theory methods, focusing on content validity, internal consistency, and structural validity.
Results: The final Comp-WARMaA instrument comprised 40 items covering four competence domains: objective knowledge, perceived knowledge, attitudes and values, and case-based performance. Content validity was confirmed by experts. Internal consistency was acceptable across subscales. Principal component analysis supported the multidimensional structure, whereas confirmatory factor analyses (CFA) and Rasch analyses yielded mixed findings, indicating the need for further refinement and psychometric testing in independent samples.
Conclusions: The Comp-WARMaA instrument demonstrated strong content validity and acceptable internal consistency. Structural analyses yielded mixed findings, indicating the need for further refinement and psychometric testing in independent samples. The instrument provides a structured framework for assessing OHNs’ competence in WARMA and may inform systematic competence evaluation and professional development in occupational health nursing.
Clinical trial number: Not applicable.
Supplementary Information: The online version contains supplementary material available at 10.1186/s12912-026-04622-y.
Keywords: Clinical competence; Occupational health nursing; Psychometrics; Surveys and questionnaires; Work capacity evaluation.